Pengembangan Bahan Ajar IPAS Berbasis Steam Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Muh. Sutrisna Kurniawan; Nuraini Nuraini; Shaibul Ahyan (Universitas Hamzanwadi, 2026)
This study aims to develop and test the feasibility, practicality, and effectiveness of STEAM-based Student Worksheets (LKPD) in science lessons, improving critical thinking skills of fifth-grade elementary school students. This study uses the (R&D) method with the 4-D model (Define, Design, Develop, Disseminate). The trial subjects were fifth-grade students of SD Negeri 3 Borok Toyang. Data were collected through expert validation sheets, teacher and student response questionnaires, observations, and critical thinking ability tests. Data were analyzed quantitatively and qualitatively. The results of the language, material, and design expert validation were 80%, 88%, and 81%, respectively, the LKPD was declared very feasible. The results of the teacher and student response questionnaires with a feasibility percentage reached 94.6% and 95.8%. The results of the effectiveness test showed a significant increase in critical thinking skills, the N-Gain value was 0.6 (60%) and classical completeness was 70%, the small group test increased to 100%. The conclusion of this study is that the STEAM-based LKPD developed is stated to be very valid, practical, and effective in improving students' critical thinking skills.